Determinan Produksi, Konsumsi dan Harga Ubi Kayu Indonesia (Studi Tahun 1991-2013 dengan Menggunakan Persamaan Simultan) - Kristian S (Inovasi Pembangunan : Jurnal Kelitbangan, 2015)
With great economic potential of cassava in the world trade and the increasing world demand for cassava as well as the limitations of Indonesia to increase cassava production it needs to be investigated factors that can affect the production, consumption and prices of cassava in Indonesia. Cassava production is significantly influenced by the variable price of cassava, cassava harvested area and price of urea fertilizer. Consumption of cassava in Indonesia is significantly influenced by population of Indonesia. The price of cassava in Indonesia is significantly influenced by cassava harvested area, consumption of cassava and the length of tarred road. Based on projections, cassava production would increase if cassava price, cassava land productivity and harvested area are improved. Indonesian cassava consumption is projected to decline if there are increasing in cassava price, per capita income and population of Indonesia simultaneously. The price of cassava is projected to increase if the consumption of cassava decreased accompanied by a decrease in the total area harvested cassava.